The Innovation of Using Flashcards in Increasing Effectiveness of Teaching Method Through the Assistance of Hijaiah Recognition Program at Matabubu Subdistrict - Hakiki Ernawati; Marisa Dwi Adiningsih; Andriano; Budi Santoso; Tiara Dian Nusantari; Dr. Hj. Erni Qomariyah, M. Si. (International Journal of Regional Innovation, 2022)
Matabubu Village is a village located in Poasia District, Kendari City, Southeast Sulawesi which has the problem of low ability to recognize hijaiah among children who are at the age of golden age. An unattractive teaching system and inappropriate use of media and lack of attention from parents cause children's low enthusiasm in learning to recognize hijaiah. Therefore, it is very important in providing fun teaching hijaiah for children in Matabubu Village, especially Lamasa Street by using audio-assisted flashcards media. This program aims to create fun learning activities and create an interactive social environment for children. The method used in this program is P2R including mentoring, teaching, and consultation room through a combination of playing and learning. Assistance is carried out to stimulate children to be more enthusiastic, teaching activities in recognizing hijaiah and involving parents in the consultation room to find out the child's development. The results of the program within a period of 3 (three) months for 16 meetings showed that children were very responsive to flashcards. The results of the program evaluation showed a success rate of 85.2%, namely the achievement of children's success in mastering amaliyah content consisting of amaliyah practices, prophet stories, and memorizing daily prayers of 80.8%, while the achievement of children's success in recognizing hijaiah was 89.6%. The program is equipped with a program implementation guidebook that has an ISBN 978-623-91098-9-9.